Proceedings of the 2nd Workshop on New Frontiers in Summarization 2019
DOI: 10.18653/v1/d19-5402
|View full text |Cite
|
Sign up to set email alerts
|

Summary Level Training of Sentence Rewriting for Abstractive Summarization

Abstract: As an attempt to combine extractive and abstractive summarization, Sentence Rewriting models adopt the strategy of extracting salient sentences from a document first and then paraphrasing the selected ones to generate a summary. However, the existing models in this framework mostly rely on sentence-level rewards or suboptimal labels, causing a mismatch between a training objective and evaluation metric. In this paper, we present a novel training signal that directly maximizes summary-level ROUGE scores through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…These work usually instantiate their encoder-decoder architecture by choosing RNN (Nallapati et al, 2017;Zhou et al, 2018), Transformer Zhong et al, 2019b;Liu and Lapata, 2019;Zhang et al, 2019b) or Hierarchical GNN as encoder, autoregressive (Jadhav and Rajan, 2018;Liu and Lapata, 2019) or nonautoregressive (Narayan et al, 2018;Arumae and Liu, 2018) decoders. The application of RL provides a means of summary-level scoring and brings improvement (Narayan et al, 2018;Bae et al, 2019).…”
Section: Extractive Summarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…These work usually instantiate their encoder-decoder architecture by choosing RNN (Nallapati et al, 2017;Zhou et al, 2018), Transformer Zhong et al, 2019b;Liu and Lapata, 2019;Zhang et al, 2019b) or Hierarchical GNN as encoder, autoregressive (Jadhav and Rajan, 2018;Liu and Lapata, 2019) or nonautoregressive (Narayan et al, 2018;Arumae and Liu, 2018) decoders. The application of RL provides a means of summary-level scoring and brings improvement (Narayan et al, 2018;Bae et al, 2019).…”
Section: Extractive Summarizationmentioning
confidence: 99%
“…As we all know, the autoregressive paradigm faces error propagation and exposure bias problems (Ranzato et al, 2015). Besides, reinforcement learning is also introduced to consider the semantics of extracted summary (Narayan et al, 2018;Bae et al, 2019), which combines the maximum-likelihood cross-entropy loss with the rewards from policy gradient to directly optimize the evaluation metric for the summarization task. Recently, the popular solution is to build a summarization system with two-stage decoder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…proposes a decoder that jointly learns to score and select sentences, while (Zhang et al, 2018) presents a latent variable extractive summarization model, which directly maximizes the likelihood of human summaries. In recent works, models based on pretrained models Bae et al, 2019;Zhang et al, 2019), especially BERT, have made a step forward.…”
Section: Extractive Summarizationmentioning
confidence: 99%
“…Recent works Bae et al, 2019;Zhang et al, 2019) have demonstrated that it is highly beneficial to apply pretrained language models such as BERT to extractive summarization models. Following this trend, we adopt a BERT-based encoder to generate contextualized representations for further extraction.…”
Section: Introductionmentioning
confidence: 99%